Establishment and correlation of age specific reference range of psa and psa density in patients of benign prostatic hyperplasia - Harjinder Singh; Maninder Kaur; Harpreet Kaur (GMC Patiala Journal of Research and Medical Education, 2019)
Prostate specific antigen (PSA) is a 34-kDa serine protease that is produced by both benign and malignant prostatic epithelial cells. PSA has assumed an increasing role in the diagnosis and management of prostate cancer. Both benign and malignant prostate tissue elaborates PSA; therefore the possibility exists for benign processes such as prostatic hyperplasia. Aims and objectives: To estimate serum PSA in 100 patients of Benign Prostatic Hyperplasia (BPH) in various age groups. To estimate the serum PSA in 50 healthy age– matched males. To correlate serum PSA levels in different age groups with volume of prostate gland and prostate density in above 150 cases. Material and Methods: The present hospital based observational and analytical study was conducted in the Department of Biochemistry, Government Medical College, Patiala in collaboration with the Department of Urology Rajindra Hospital, Patiala on 100 patients reporting to Department of Urology with diagnosed BPH and presenting with Lower Urinary Tract Symptoms (LUTS), Rajindra Hospital, Patiala. Results and Conclusion : With increase in age there was increase in size (volume) of the prostate. PSA values were also increased in patients of BPH. An inverse correlation of PSA with PSAdensity was observed in patients of BPH because volume /size of the prostate was increased with increasing age.